A numerical study of the response of blast loaded thin circular plates, with both clamped and integral boundary conditions - Gelman, Mark Ernest (University of Cape Town, 2014)
Includes bibliographical references. === This report sets out the results of a numerical investigation into the response of thin circular plates subjected to impulsive loads, using the commercial finite element code ABAQUS. iv Previous theoretical and numerical predictions of plate response have assumed a fully constrained boundary condition, while experiments have involved the use of both clamped and integral (fully built-in) boundary conditions. The current analysis employs 4-noded continuum elements in the finite element model, that allow the experimental boundary conditions to be modelled closely. Fully built-in plates are modelled by the inclusion of a material boundary, and clamped plates by the use of rigid clamping elements and a simple friction condition between the clamps and the plate surface. The inclusion of fillet radii at the integral boundary, and an edge radius at the clamped boundary, have been reported in additional experiments. These modifications are also modelled in the current investigation. The finite element model incorporates non-linear geometry and material effects, and strain rate sensitivity is included in the viscoplastic material definition. Impulsive loading is implemented through short duration pressure pulses, while the use of a uniform initial velocity profile is also shown to give good results. An explicit time integration scheme is used for the dynamic structural response.